Pigmented Lesions of Skin: A Histopathologic Experience at a Tertiary Care Center in Central Nepal - Goyal, Binita; Rai, Suman; Sedhain, Mamata; Subedi, Pratigya (Journal of College of Medical Sciences-Nepal, 2021)
Introduction Pigmented skin lesions refer to lesions that are brown, black or blue in color. These are not always melanocytic in origin. Keratinocytic, vascular or reactive pigmentation in other lesions can also appear pigmented. The main aim of the study was to see the histopathological spectrum and objective was to compare clinical and histopathological diagnoses in pigmented skin lesions. Methods This descriptive study was carried out on 43 pigmented skin lesions that were biopsied over a 1 and half year period from Jan 2018 to June 2019 in College of Medical Sciences and Teaching Hospital. Results Age of the patient ranged from 10 to 88 years and mean±SD was 42.02±19.73 years. There were 21 (48.8%) males and 22 (51.2%) females with a male female ratio 0.9:1. Melanocytic nevus was the most common histopathological diagnosis (11 cases, 25.6%). Reactive pigmentation was seen in 20 (46.5%) cases. Malignant cases comprised 6 (14.0%) cases which included 2 (4.7%) cases of melanoma, 2 (4.7%) cases of pigmented basal cell carcinoma and 1 (2.3%) case each of basaloid squamous cell carcinoma and trichoblastic carcinoma each. Clinicopathological agreement could be seen in 32 (74.4%) cases. However, malignancy was clinically suspected in only half of histologically diagnosed cases. Conclusions Melanocytic nevi were the most common pigmented lesions diagnosed. Not all pigmented lesions are melanocytic in origin. Malignant tumors can sometimes appear deceptively benign and also tumors other than melanoma can be pigmented. Hence, histopathological examination remains the gold standard in diagnosing these conditions and guiding appropriate management. Keywords: melanocytic; melanoma; nevus; pigmented.